2017
DOI: 10.7717/peerj.3808
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin longa extract-loaded nanoemulsion improves the survival of endotoxemic mice by inhibiting nitric oxide-dependent HMGB1 release

Abstract: BackgroundHigh mobility group box 1 (HMGB1) is a well-known damage-related alarmin that participates in cellular inflammatory responses. However, the mechanisms leading to HMGB1 release in inflammatory conditions and the therapeutic agents that could prevent it remain poorly understood. This study attempted to examine whether the Curcumin longa herb, which is known to have anti-inflammatory property, can modulate cellular inflammatory responses by regulating HMGB1 release.MethodsThe murine macrophage RAW264.7 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 31 publications
1
13
0
Order By: Relevance
“…Ahn et al () found that curcumin has the ability to suppress NO signaling and reduce the release of the proinflammatory cytokine.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ahn et al () found that curcumin has the ability to suppress NO signaling and reduce the release of the proinflammatory cytokine.…”
Section: Resultsmentioning
confidence: 99%
“…There was also an increase in the phosphorylation of p38 and caspase-3 activity. Ahn et al (2017) found that curcumin has the ability to suppress NO signaling and reduce the release of the proinflammatory cytokine. Yuan et al (2012) have investigated the effects of curcumin on triggering receptor expressed on myeloid cells 1 (TREM-1) expression in response to LPS.…”
Section: In Vitro Studiesmentioning
confidence: 99%
“…Several phytochemicals have been shown to alleviate the sepsis during interfering with the release and action of HMGB1. (I) resveratrol inhibits the cytoplasmic translocation of HMGB1; (II) resveratrol, 56,57 curcumin, 95 quercetin, 42 and glycyrrhizin 24 decrease the level of HMGB1; and (III) glycyrrhizin directly binds HMGB1 and inhibits its binding to RAGE and TLR4 24,25 …”
Section: Discussionmentioning
confidence: 99%
“…in vivo studies also showed that the curcumin nanoemulsion increased the survival rate by up to 50% in LPS‐challenged mice. This was attributed to blocking NO signaling as was evidenced by a dramatic decrease of circulatory HMGB1, as well as reduced expression of iNOS in kidney, lung, heart, and liver tissues of endotoxemic mice 95 …”
Section: Treatment Of Sepsis With Polyphenolic Compoundsmentioning
confidence: 99%
“…Administration of neutralizing antibodies or antagonists to HMGB1 ameliorated the inflammation‐associated symptoms in sepsis, ischemic reperfusion, and colitis (Andrassy et al., 2008; Davé et al., 2009; Wang et al., 1999). Recent studies demonstrated that extracts derived from medicinal herbs such as Curcumin longa and Dalbergia odorifera , ameliorates the LPS‐triggered lethality in the endotoxemia mouse model through nitric oxide (NO) signal‐mediated regulation of HMGB1 release (Ahn, Hwang, Lee, et al., 2017; Choi et al., 2017). Furthermore, formononetin, a herbal isoflavonoid, inhibited LPS‐triggered release of HMGB1 by upregulating SIRT1 (sirtuin 1; silent mating type information regulation 2 homologue 1) in a peroxisome proliferator‐activated receptor (PPAR)δ‐dependent manner (Hwang et al., 2018).…”
Section: Introductionmentioning
confidence: 99%